2021
DOI: 10.3390/ijerph19010188
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Care during COVID-19 in the UK: Perspectives of Healthcare Professionals on Impacts on Care Quality and Staff Well-Being

Abstract: In light of the rapid changes in healthcare delivery due to COVID-19, this study explored kidney healthcare professionals’ (HCPs) perspectives on the impact of these changes on care quality and staff well-being. Fifty-nine HCPs from eight NHS Trusts across England completed an online survey and eight took part in complementary semi-structured interviews between August 2020 and January 2021. Free-text survey responses and interviews were analysed using inductive thematic analysis. Themes described the rapid ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, based on patient and healthcare professionals' (HCPs) interviews, it was found that the quality of health services was not satisfactory. More than one in three participants described difficulties in HCP-patient communication, there were also delays in patients receiving appropriate treatment leading to sub-optimal care ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, based on patient and healthcare professionals' (HCPs) interviews, it was found that the quality of health services was not satisfactory. More than one in three participants described difficulties in HCP-patient communication, there were also delays in patients receiving appropriate treatment leading to sub-optimal care ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data on the impact of COVID-19 on people living with CKD and kidney healthcare provision during the pandemic are reported elsewhere [ 32 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…2 Psychological well-being of the EM workforce is compromised, with working conditions recognised as playing a key role. 6 7 Staff attrition has a systemic impact: lower staff ratios lead to higher workloads, reduced quality of care, 8 higher levels of medical errors 9 and poorer staff well-being, 10 all factors associated with staff absence and intention to leave. 11 The landscape of EM has also changed; increased prevalence of high patient acuity, multimorbidity and an ageing population all bear considerable impact.…”
Section: Introductionmentioning
confidence: 99%